Dynamics of Underground River Development by Allogenic Recharge in the Tropical Gunungsewu Karst Area, Indonesia - Cahyadi, Ahmad; Haryono, Eko; Adji, Tjahyo Nugroho; Widyastuti, Margaretha (Iraqi Journal of Science, 2025)
Dissolving cavities in a water-holding rock (karst aquifer) are tied to how water is stored and released. However, cavity development by allogenic water is rarely studied. This research was intended to analyze the dynamic development of dissolution cavities in tropical karst areas influenced by allogenic recharge, using Beton Spring as an example. These dynamics were determined from water corrosiveness or aggressiveness based on the calcium carbonate saturation index, dissolution rate, and cavity development rate according to wall retreats. We found that water becomes more corrosive at the start of the rainy season due to the piston effect. The dissolution rate in the Karst Drainage Basin of Beton (Beton KDB) was estimated at 33.60 m3/km2/year or faster than in KDBs without allogenic recharges. Further, the mean rate of solutional wall retreat was calculated at 0.02 cm/year, or greater than the global average of approximately 0.01 cm/year.